Spotlight on CKD deaths—increasing mortality worldwide - Rhee, Connie M.; Kovesdy, Csaba P. (Nature reviews. Nephrology, 2015)
In the USA, mortality among patients with chronic kidney disease (CKD) and end-stage renal disease has declined over the past two decades. By contrast, new data indicate that the rate of CKD-associated deaths is increasing worldwide. This important finding highlights CKD as a major contributor to global morbidity and mortality.